The Contribution of Disgust in Contamination Fear: The Mediating Role of Harm Avoidance and Incompleteness - Árný Árnadóttir 1991-; Sólveig Anna Daníelsdóttir 1992- (2016)
The objective of the study was to examine the contribution of disgust in contamination fear. In addition, the aim was to determine if the relationship between disgust and contamination fear is partly mediated by incompleteness and harm avoidance. Participants were 84 students enrolled at the University of Iceland. They were asked to answer questionnaires measuring disgust, contamination fear, harm avoidance and incompleteness among other constructs. A behavioral avoidance task (BAT) was then administered, measuring approach and avoidance behaviors. As predicted, results showed that both harm avoidance and incompleteness mediate the relationship between disgust and contamination fear using self-report measures, indicating that contamination-related OCD may be both sensation based as well as driven by cognitive distortions. However contrary to predictions, these results were not replicated in an experimental setting. Additional analyses showed that as expected disgust was a stronger predictor of contamination fear than anxiety. In addition disgust, but not anxiety, predicted the urge to wash as well as avoidant behavior in the BAT. The results indicate that disgust contributes to contamination fear. It is possible that individuals with contamination OCD perform their compulsions in order to reduce a sensation of disgust rather than to get rid of their anxiety or fear.